PENGARUH PENDIDIKAN KEWIRAUSAHAAN, MOTIVASI BERWIRAUSAHA DAN SELF-EFFICACY TERHADAP PEMBENTUKAN SIKAP KEWIRAUSAHAAN MAHASISWA - Mustikasari Sara; Riza Yonisa Kurniawan (PROMOSI: Jurnal Program Studi Pendidikan Ekonomi, 2021)
The purpose of this research to analyze the influence of entrepreneurship education, entrepreneurial motivation, and self-efficacy on the formation of student entrepreneurial attitudes. The research subjects in this research were all students of the Economics Education Study Program, Faculty of Economics, State University of Surabaya, Class of 2017 who had taken entrepreneurship courses with a total of 83 students. Data were collected using a questionnaire instrument which was distributed to respondents. Data analysis in this research using multiple linear regression. The results show that partially entrepreneurship education has a significant effect on the formation of student entrepreneurial attitudes, entrepreneurial motivation has no significant effect on the formation of student entrepreneurial attitudes, and self-efficacy has a significant effect on the formation of student entrepreneurial attitudes. Meanwhile, simultaneously the results showed that entrepreneurship education, entrepreneurial motivation and self-efficacy had a significant effect on the formation of student entrepreneurial attitudes.Keywords : Entrepreneurial Motivation; Entrepreneurship Education; Self-efficacy; Entrepreneurial Attitude